Bio-purification of sugar industry wastewater and production of high-value industrial products with a zero-waste concept. Issue 21 (25th November 2021) - Nawaz, Muhammad Zohaib; Bilal, Muhammad; Tariq, Arslan; Iqbal, Hafiz M. N.; Alghamdi, Huda Ahmed; Cheng, Hairong
Abstract: In recent years, biorefinery approach with a zero-waste concept has gained a lot research impetus to boost the environment and bioeconomy in a sustainable manner. The wastewater from sugar industries contains miscellaneous compounds and need to be treated chemically or biologically before being discharged into water bodies. Efficient utilization of wastewater produced by sugar industries is a key point to improve its economy. Thus, interest in the sugar industry wastes has grown in both fundamental and applied research fields, over the years. Although, traditional methods being used to process such wastewaters are effective yet are tedious, laborious and time intensive. Considering the diverse nature of wastewaters from various sugar-manufacturing processes, the development of robust, cost-competitive, sustainable and clean technologies has become a challenging task. Under the recent scenario of cleaner production and consumption, the biorefinery and/or close-loop concept, though using different technologies and multi-step processes, namely, bio-reduction, bio-accumulation or biosorption using a variety of microbial strains, has stepped-up as the method of choice for a sustainable exploitation of a wide range of organic waste matter along with the production of high-value products of industrial interests. This review comprehensively describes the use of various microbial strains employed for eliminating the environmental pollutants from sugar industry wastewater. Moreover, the main research gaps are also critically discussed along with the prospects for the efficient purification of sugar industry wastewaters with the concomitant production of high-value products using a biorefinery approach. In this review, we emphasized that the biotransformation/biopurification of sugar industry waste into an array of value-added compounds such as succinic acid, L-arabinose, solvents, and xylitol is a need of hour and is futuristic approach toward achieving cleaner production and consumption.